Costi del trattamento con oloprazina nelle fasi iniziali della schizofrenia - Berardi, Domenico; Dell’Atti, Maddalena; Russo, Francesca; Vagnini, Virginia; Guidi, Luca; Edgell, Eric T. (Farmeconomia. Health economics and therapeutic pathways, 2002)
Objective: In Italy, use of olanzapine in the public sector was limited by law to patients that had failed treatment with conventional antipsychotics, due to the higher purchase price of the drug. This restriction prevented first-episode patients and patients early in the course of their illness from being treated with olanzapine. The present study investigates economic consequences of this policy. Design: The present study retrospectively outlines treatment costs of patients switched to olanzapine during the early stages of schizophrenia as compared to the costs of patients switched during a later stage of the illness. Setting: The study was conducted within Italian Community Mental Health Services. Patients: The cost of pharmacological and non-pharmacological treatment was retrospectively calculated in 25 out-patients with schizophrenia and related disorders over a one-year span. Thirteen patients were switched to olanzapine in the early stage of their illness, prior to drug approval under a compassionate use regimen. Twelve patients started olanzapine under the restriction in a later stage of illness following failed treatment with a conventional antipsychotic. Results: While total treatment costs between the two groups was similar, cost distribution was different. Early Switch patients had higher drug costs and higher rehabilitation costs, while Late Switch patients had higher hospitalisation costs. Conclusions: Small patient numbers and design limitations prevent conclusions being drawn regarding the ultimate impact on outcome and total treatment cost of restriction of olanzapine to second-line use. Despite this, our findings demonstrate that within the context of the Italian CMHS, patients treated with olanzapine while still in the early stages of schizophrenia do not necessarily cost more overall compared to patients who receive olanzapine after failing treatment with a conventional antipsychotic.